Analisis Distribusi Risiko Rantai Pasok Kopi Organik Gayo Menggunakan Pendekatan Indeks Risiko - Arie Saputra; Taufik Djatna (Jurnal Optimalisasi, 2026)
This study aims to analyze risk in the organic coffee supply chain by examining the level and distribution of risk across key actors. The scope of the research covers upstream to downstream participants, including farmers, collectors, processors, and cooperatives. A quantitative approach was employed using a risk index model that integrates probability and consequence to measure risk exposure at each stage of the supply chain. Data were collected through field surveys, interviews, and secondary sources, and subsequently analyzed to generate comparative risk values among actors. The results indicate that risk is unevenly distributed, with farmers at the upstream level exhibiting the highest risk index (approximately 0.32), while downstream actors such as cooperatives show relatively lower risk levels (around 0.14). The dominant risks are associated with production uncertainty, quality variability, and price fluctuations, which disproportionately affect upstream actors. These findings demonstrate that risk characteristics are strongly influenced by the structural position and functional role of each actor within the supply chain. In conclusion, the study highlights that supply chain risk analysis should not only focus on identifying and measuring risk magnitude but also on understanding its distribution across actors to provide a more comprehensive assessment of system vulnerability.